The walking dead. Vol. 10, What we become - Kirkman, Robert (Kirkman, Robert. Walking dead, 2009)
Police officer Rick Grimes is shot on the job and wakes up a month later to find that the world that he knows is gone. Zombies have taken over and are killing and eating those who are still alive. He sets out toward Atlanta in the hope that his family is still alive and endures many horrors along the way.